A study on the willingness to pay for "Solar Home System" of residents in Barangay 27, Tacloban City as alternative renewable source of electricity service connection - Bibat, James Char B.; Nebril, Raizza D.
The purpose of this study is to determine the willingness to pay the households of Brgy. 27 Tacloban City for a solar home system as an alternative source of renewable electricity as well as the factors affecting the Willingness to Pay (WTP) of the consumers for a solar home system. This was achieved following a mix of qualitative and quantitative methods to randomly collect primary data from 72 respondents using a carefully designed questionnaire survey. Results of the study revealed that at prevailing conditions, the respondent on average is willing to pay P2,158,296.601 for an installation of a solar home system. Moreover, based on the results of the odds ratio it revealed that the knowledge about the solar home system, price sensitivity, and environmental awareness are strongly associated with a higher willingness to pay. On the other hand, household size, educational attainment, and brand quality and reliability perceptions are associated with a lower willingness to pay. Household income, based on the odds ratio provided, seems to have a minimal effect on the willingness to pay. This research study acts as a guide assisting energy policy-makers, government agencies, and investors in designing better-targeted public awareness and marketing campaigns on renewable energy technologies specifically on solar panels. This is in turn will assist in achieving two of the Sustainable Development Goals (SDGs); Affordable and Clean Energy (Goal 7) and Climate Action (Goal 13) and contribute to the Ambisyon Natin 2040 goals of the Philippines.